STRATEGI LITERASI MEMBACA DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH DASAR : STUDI PUSTAKA - Syifa Ullia; Rizka Amira; Nia Astuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading literacy is a fundamental skill that plays a crucial role in supporting learning success at the elementary school level. The Merdeka Curriculum positions reading literacy as a cross-curricular competence that should be systematically integrated into the learning process. However, the implementation of reading literacy strategies within the Merdeka Curriculum framework still faces various challenges, particularly in terms of effective instructional strategies, teacher roles, and school environment support. This study aims to comprehensively examine reading literacy strategies in the implementation of the Merdeka Curriculum at elementary schools through a library research approach. The research employed a qualitative method using documentation techniques to collect data from relevant scientific literature, including journal articles, books, and educational policy documents published within the last ten years. The data were analyzed using content analysis to identify key themes related to reading literacy strategies. The findings indicate that differentiated instruction, meaningful text-based learning, the integration of media and technology, as well as the strengthened roles of teachers and a literacy-rich school environment significantly contribute to improving students’ reading literacy. These results highlight the importance of a holistic integration of reading literacy strategies in implementing the Merdeka Curriculum at the elementary school level.